Analisis Konflik Sosial Dalam Cerpen “Panggung Terakhir” Karya M Rosyid HW - Desta Ramadani Fitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Social conflict usually occurs because competition in the economic field, such as competition for resources or jobs, can cause conflict between competing groups. This research explains the forms, causes and impacts in the short story